Quantifying nitrogen in GeSbTe:N alloys. Issue 4 (24th January 2020) - Jeynes, C.; Nolot, E.; Costa, C.; Sabbione, C.; Pessoa, W.; Pierre, F.; Roule, A.; Navarro, G.; Mantler, M.
Abstract : Result of measured N-content in test set of Ge2 Sb2 Te5 :N samples. XRF calibrated using a set of reference materials certified by IBA. Abstract : We have calibrated on-site WD-XRF (wavelength-dispersive X-ray fluorescence) measurements of GeSbTe:N (GST-N) stoichiometry with off-site accurate ion beam analysis (IBA). N is determined by elastic backscattering spectrometry (EBS) using the resonance at 3.7 MeV in the 14 N(α, α) 14 N reaction. Ge and Sb + Te are determined by Rutherford backscattering spectrometry (RBS) separately but self-consistently with the resonant EBS: the Sb/Te ratio can be determined by RBS but not with useful precision. The XRF instrumental function is determined using pure metal standards and the spectra are quantified using fundamental parameters code. We find that, as expected, for both Ge and (Sb + Te) the heavy elements are determined accurately by XRF (within the uncertainties), but for N the standardless XRF has non-linear errors around 10%. Using the absolute N content determined by IBA a calibration curve is obtained allowing N determination by WD-XRF at a precision of about 1% and an absolute accuracy (traceable through IBA) of about 4% for GST films with N content between 4–20 at%. The IBA measurement precision of the N content of the GST-N XRF calibration samples is 0.4 at% (that is, a relative precision ranging from 10% to 2% for N contents between 4–20 at%).